(untitled) (Journal of the College of Education for Women, 2019)
This study aims at investigating the partial Islamic rules of preparing and distributing cartoons in order to issue an overall Islamic rul. To reach an end, descriptive and analytical approaches are adopted to clarify the nature of cartoons and other related concepts. The researcher, as well, with reference to verses of the Holy Quran, tradition (Hadith) and Islamic jurists, adopts a deductive approach to issue Islamic rules related to the industry of cartoons and it’s distributionThe study consists of three sections. The first Section addresses the following issues: Definition animation; and related wordy. The second Section: Origin of Cartoon’s history and it’s negative and positive effects. The third Section: Islamic rules related to watching cartoons.The study comes to following conclusions: as long as cartoons abide by Islamic rules, preparing, distributing, establishing TV channels, and watching cartoons are all religiously lawful (Halal); in addition, Islam recognizes the author’s and broadcaster’s rights as long as they abide by Islamic rules as well